Antibacterial Activity of Gels with Pomegranate, Apricot and Green Tea Glycolic Extracts - Calixto, Giovana, Vieira, Daniela C.M., Fiúza, Thalita F.M., Salgado, Hérida R, Chorilli, Marlus (Journal of Applied Pharmaceutical Science)
Pomegranate (PGE) and green tea (GTGE) glycolic extracts are being employed in formulations because of their antiseptic and astringent effects. Apricot (AGE) glycolic extract possesses function cooling and antibacterial. The aim was to verify the antibacterial activity of these extracts incorporated in gel base. The antibacterial activity was verified by diffusion in agar method, using cylinder in plate. Plates containing Staphylococcus aureus (ATCC 6538p), Pseudomonas aeruginosa (ATCC 27853), Escherichia coli (ATCC 10536) and Salmonella sp. (ATCC 19196) were incubated at 37ºC for 24 hours. After incubation, the results were analysed with a pachymeter, observing the bacterial growth inhibition halo diameter and the statistical significance level was determined. PGE presented activity only against P. aeruginosa; GTGE presented activity against S. aureus, P. aeruginosa and E. coli; and AGE presented activity against P. aeruginosa and Salmonella sp. According to the experimental conditions, it is possible to conclude that GTGE presented the greater growth inhibition halo diameter when compared with other extracts, suggesting higher antibacterial action of this extract.
Keywords: Antibacterial activity,Gels,Glycolic extracts,Pomegranate,Green Tea.